The use of dexmedetomidine in suppressing cardiovascular response due to intubation in general anesthesia - Zulfikar, Zulfikar (Universitas Wiralodra, 2024)
Endotracheal intubation is commonly used to maintain a safe airway during general anesthesia. This intubation action can trigger a dangerous response for the patient, one of which is the cardiovascular system. Increases in arterial blood pressure, plasma catecholamine levels, and heart rate are responses that can occur during intubation. Therefore, various methods and treatments have been used to control this cardiovascular response, including dexmedetomidine. Dexmedetomidine is a highly selective α2-adrenergic receptor agonist that has analgesic, sympatholytic, and sedative effects with minimal depression of ventilation. Much research has been done on how well dexmedetomidine works to stop the cardiovascular response to intubation. Dexmedetomidine was significantly associated with reductions in heart rate, systolic blood pressure, and MAP.